Definition and delimitation of peripheries of Visegrad countries - Novotný, Ladislav; Mazur, Marcin (1982– ); Egedy, Tamás (IGiPZ PAN, 2015)
The aim of this article is to analyze various methods and approaches to peripherality, and to introduce proposals for delimitation of peripheral areas in Visegrad countries. First, the content of approaches to the identification of peripherality is assessed, followed by emphasis on the role of spatial scale in the delimitation of peripheral areas. Then, the strict and broad understanding of peripherality is described considering the role of locality in its conceptualization. The quantitative approach to the delimitation of peripheries in the Visegrad countries presented in the following part of the article is in line with the precise understanding, as it is assumed to be more sufficient for the research of economic development in peripheral areas. In the final part of the article, examples of delimitation of peripheries in whole V4 area are introduced based on distance-based measures, equidistant-based measures, and on the approach employing the potential index. This allowed for revealing and validating some regularities in the spatial distribution of peripheral areas but also revealed the role of subjective assumptions entering the delimitations.
24 cm
Keywords: peripherality; marginality; locality; Visegrad countries; peripheral areas

Wiejskie obszary peryferyjne - uwarunkowania i czynniki aktywizacji = Peripheral rural areas - conditions and factors stimulating to activity - Wesołowska, Monika. Red. (PAN IGiPZ, 2011)
250 pp. : il. ; 24 cm
Summary in English.
Publikacja finansowana ze środków Wydziału Nauk o Ziemi i Gospodarki Przestrzennej UMCS
Bibliogr.
Keywords: biography of Władysława Stola; bibliography of Władysława Stola; rural population; local society; rural areas; peripheral areas; regional policy; Poland